2017
DOI: 10.1186/s12879-017-2183-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of laboratory confirmed measles virus cases in the southern nations of Ethiopia, 2007–2014

Abstract: BackgroundIn Ethiopia, measles case-based surveillance was introduced in 2004 as one strategy for measles control by laboratory confirmation of suspected cases. In this article, epidemiological distribution of laboratory-confirmed measles cases were reported from the Southern Nation Nationalities and Peoples Region (SNNPR) of Ethiopia between 2007 and 2014, as the region is one of the highly measles affected areas in Ethiopia.MethodA serum sample was collected from all measles suspected cases, and patient info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
1
11
2
Order By: Relevance
“…Our finding showed 40% of tested samples in this surveillance system had positive results for measles IgM. This result was higher than similar studies done in Ethiopia´s Amhara and Southern Nations Nationalities and Peoples (SNNP) regions [ 28 , 32 ] within a similar timeframe. The number and percentage of positive and negative measles IGM results were observed fluctuating throughout the years.…”
Section: Discussioncontrasting
confidence: 68%
“…Our finding showed 40% of tested samples in this surveillance system had positive results for measles IgM. This result was higher than similar studies done in Ethiopia´s Amhara and Southern Nations Nationalities and Peoples (SNNP) regions [ 28 , 32 ] within a similar timeframe. The number and percentage of positive and negative measles IGM results were observed fluctuating throughout the years.…”
Section: Discussioncontrasting
confidence: 68%
“…From 2013-2019 the highest measles prevalence rates were seen in 2015 and 2019 accounted for 21 per 100,000 and 141 per 100,000 populations respectively. The study nding is higher compared to study conducted in Nigeria the incidence was estimated at 19/100,000 population/year (22) and in Ethiopia the incidence was more than 2/100,000 populations/year for ve years (21). The deference is possibly due to high accumulation of susceptible person and outbreak occurs frequently in the zone.…”
Section: Discussionmentioning
confidence: 60%
“…Several studies have focused on the consistency of DBS as an analyte for HCV diagnosis. A meta-analysis about diagnosis accuracy of serological assays using DBS reported a pooled estimated sensitivity of 98% and specificity of 99% [ 26 ]. Soulier et al revealed that HCV RNA levels in DBS were lower than in serum and all patients were correctly genotyped using DBS [ 27 ].…”
Section: Discussionmentioning
confidence: 99%